Anaplasma phagocytophilum prevalence in ticks and rodents in an urban and natural habitat in South-Western Slovakia - Svitálková, Zuzana; Haruštiaková, Danka; Mahríková, Lenka; Berthová, Lenka; Slovák, Mirko; Kocianová, Elena; Kazimírová, Mária (Parasites & vectors, 2015)
BACKGROUND: Ixodes ricinus is the principal vector of Anaplasma phagocytophilum, the ethiological agent of granulocytic anaplasmosis in Europe. Anaplasmosis is an emerging zoonotic disease with a natural enzootic cycle. The reservoir competence of rodents is unclear. Monitoring of A. phagocytophilum prevalence in I. ricinus and rodents in various habitat types of Slovakia may contribute to the knowledge about the epidemiology of anaplasmosis in Central Europe. METHODS: Over 4400 questing ixodid ticks, 1000 rodent-attached ticks and tissue samples of 606 rodents were screened for A. phagocytophilum DNA by real-time PCR targeting the msp2 gene. Ticks and rodents were captured along six transects in an urban/suburban and natural habitat in south-western Slovakia during 2011-2014. Estimates of wildlife (roe deer, red deer, fallow deer, mouflon, wild boar) densities in the study area were taken from hunter's yearly reports. Spatial and temporal differences in A. phagocytophilum prevalence in questing I. ricinus and relationships with relative abundance of ticks and wildlife were analysed. RESULTS: Overall prevalence of A. phagocytophilum in questing I. ricinus was significantly higher in the urban/suburban habitat (7.2%; 95% CI: 6.1-8.3%) compared to the natural habitat (3.1%; 95% CI: 2.5-3.9%) (χ(2) = 37.451; P < 0.001). Significant local differences in prevalence of infected questing ticks were found among transects within each habitat as well as among years and between seasons. The trapped rodents belonged to six species. Apodemus flavicollis and Myodes glareolus prevailed in both habitats, Microtus arvalis was present only in the natural habitat. I. ricinus comprised 96.3% of the rodent-attached ticks, the rest were Haemaphysalis concinna, Ixodes trianguliceps and Dermacentor reticulatus. Only 0.5% of rodent skin and 0.6% of rodent-attached ticks (only I. ricinus) were infected with A. phagocytophilum. Prevalence of A. phagocytophilum in questing I. ricinus did not correlate significantly with relative abundance of ticks or with abundance of wildlife in the area. CONCLUSION: The study confirms that urban I. ricinus populations are infected with A. phagocytophilum at a higher rate than in a natural habitat of south-western Slovakia and suggests that rodents are not the main reservoirs of the bacterium in the investigated area.
Keywords: Animals; Cities; nemoci hlodavců; Female; klíště; Disease Reservoirs; Rodent Diseases; zdroje nemoci; ženské pohlaví; Rodentia; nymfa; velkoměsta; Time Factors; časové faktory; Slovakia; Animal Distribution; Nymph; ehrlichióza; Male; Anaplasma phagocytophilum; ekosystém; Ecosystem; hlodavci; Slovenská republika; zvířata; mužské pohlaví; Ehrlichiosis; rozšíření zvířat; kvantitativní polymerázová řetězová reakce; Ixodes; Real-Time Polymerase Chain Reaction